Akame ga kill! 6 - Takahiro, 1981- (Yen Press, 2016)
While on a mission to exterminate a new type of Danger Beast, Tatsumi is reunited with none other than General Esdeath! With one last chance to win Esdeath over to Night Raid's side, will Tatsumi prove fruitful in his efforts?